Creating innovative flavour and texture experiences - Edwards-Stuart, Rachel (2009)
The work presented in this thesis describes the use of scientific research in the development of novel texture and flavour experiences and their potential for use in fine gastronomy. In order to create an interesting textural experience, modified celluloses were investigated. Their unique property is that they have the ability to gel at high temperatures, but return to the solution state upon cooling. This phenomena was used to test the hypothesis that hot gels made from these materials could melt at temperatures greater than mouth temperature, providing a melt-in-the-mouth sensation on consumption in a fashion analogous to gelatine. Melting temperatures of these hot gels were calculated using the techniques of rheology and differential scanning calorimetry, as well as more empirical methods, and results showed that gels made from a number of different hydroxypropylmethylcelluloses (HPMCs) displayed melting temperatures above 37°C. In order to predict their flavour release properties, the mixing efficiency of the solutions were investigated and results showed that solutions made from the lower molecular weight HPMCs showed more desirable mixing behaviour, suggesting better flavour release than those made from high molecular weight HPMCs. Furthermore, these solutions also had more desirable mouth-feel attributes, as determined by sensory analysis, yet their inherent flavour attributes were less pleasant. Therefore, modified celluloses show potential use in producing hot gels that melt in the mouth.